Analisis Pengaruh Gaya Kepemimpinan Terhadap Semangat Kerja Karyawan Studi Kasus pada KUD Gondanglegi - Ahmad Muhtar Syarofi (IQTISHODUNA: Jurnal Ekonomi Islam, 2016)
This watchfulness aims that is first, to detect leadership style at KUD Gondanglegi Malang. For company this watchfulness can give input and deliberation for KUD Gondanglegi management side, respective with decision making in employee management, so that created tall work spirit. Analyzer that used in this watchfulness that is by using scale distence analysis and simple linear regression.Watchfulness result conclusion that is style leadership exist in stone KUD Gondanglegi belongs in laissez faire leadership style. Employee work spirit exist in KUD Gondanglegi Malang enters in tall category. Test result knowable that influential leadership style significant towards employee work spirit. The mentioned provable with value t count > t table.